'All of us together in a blurred space': principles for co-creating curriculum with international partners. Issue 3 (3rd July 2018) - Bilous, Rebecca; Hammersley, Laura; Lloyd, Kate; Rawlings-Sanaei, Felicity; Downey, Greg; Amigo, Maria; Gilchrist, Samantha; Baker, Michaela
ABSTRACT: This paper shares an innovative methodology to 'co-create' a curriculum with eleven international community development organisations from seven countries to prepare undergraduate students for international work-integrated learning activities. The co-creation process was complex, messy, and always evolving. Here we reflect on and document the process, identifying three key methodological principles that might guide the co-creation process for others. These principles embrace the unpredictable, emotional, and personal reality of bringing together diverse ideas and perspectives, as well as opening up possibilities for more creative ways of communicating and listening to what is seen, heard, and felt.